Dynamic behavior of cluster observables for the 2d Ising model - Wanzeller, Wanderson G. [UNESP]; Mendes, Tereza; Krein, Gastão [UNESP] (FapUNIFESP (SciELO), 2006)
We present results of our numerical study of the critical dynamics of percolation observables for the two-dimensional Ising model. We consider the (Monte Carlo) short-time evolution of the system with small initial magnetization and heat-bath dynamics. We find qualitatively different dynamic behaviors for the magnetization M and for Ω, the so-called strength of the percolating cluster, which is the order parameter of the percolation transition. More precisely, we obtain a (leading) exponential form for Ω as a function of the Monte Carlo time t, to be compared with the power-law increase encountered for M at short times. Our results suggest that, although the descriptions in terms of magnetic or percolation order parameters may be equivalent in the equilibrium regime, greater care must be taken to interpret percolation observables at short times.
Keywords: Critical short-time dynamics; Ising model; Percolation